Evaluation of mechanical behaviour of graphene oxide grafted CFRP composites: a comparison of anodic and cathodic EPD. (31st October 2022) - Sumit Dash, Soumya; Gangineni, Pavan Kumar; Gupta K, B. N. V. S. Ganesh; Dasari, Srinivasu; Prusty, Rajesh Kumar; Ray, Bankim Chandra
ABSTRACT: In this work, graphene oxide (GO) was grafted on carbon fibre (CF) surface using anodic and cathodic electrophoretic deposition (EPD). Twelve-layer carbon fibre–reinforced polymer (CFRP) composite laminates were fabricated using the modified CFs. Morphology study of modified CFs revealed that cathodic EPD has resulted in dense and uniform deposition of nanofiller. Flexural and Short Beam Shear (SBS) tests were conducted to evaluate their flexural and interlaminar properties. Both anodic and cathodic CFRP composites have shown better mechanical performance than neat CFRP composite, with cathodic CFRP composite showing the best performance due to uniform deposition of nanofiller. Cathodic CFRP composite has shown an improvement of 7.57% and 16.12% in flexural and ILSS responses, respectively, with respect to neat CFRP composite. Differential scanning calorimetry (DSC) and fractography analysis using scanning electron microscope (SEM) were carried out to know the thermal behaviour and failure mechanism of all fabricated composites, respectively.